Application Of Role Playing Learning Model Using Image Media In Students Of MI NW Aik Anyar Sukamulia East Lombok - Muliadi; Mahsur (ASTEEC, 2023)
This research focuses on showing the application model of role playing learning by using image media in MI NW Aik Anyar Sukamulia East Lombok students. By applying the learning model, it does not escape the condition of students who are less effective in following the learning provided by the teacher. By seeing the lack of effectiveness in teaching, teachers apply the role playing learning model. This research is a Classroom Action Research, with data collection such as observation, and tests. The results found that when the teacher applied the role playing method model in cycle I to 23 students or 70% and improved again in cycle II so that student learning completeness reached 92% or 31 students. Thus it can be said that, the role playing method is a very effective method for teachers to apply in teaching MI NW Aik Anyar Sukamulia East Lombok students.